The Effect of Semiotic Scansion in Reading Achievement among the First Basic Grade Pupils - Abdulkareem Ali, Suroor; Ali Ameen, Fardous (Al-Adab Journal, 2021)
The current study aims at identifying the effect of semiotic scansion in reading achievement among the first basic grade pupils. The sample consists of 48 male and female pupils of the first basic grade in Razgary primary school in Sulaimaniyah Governorate – Chamchamal province. Thus، the sample has been distributed into two groups. The first group is called the experimental group which includes 23 male and female pupils. The second group is called control group which includes 25 male and female pupils for the year (2018 – 2019). Accordingly، the semiotic scansion has been applied on the experimental group whereas the traditional method has been used on the control group. There is a parity between them in some variables including (age –the marks of Kurdish reading of the first term). The two researchers have conducted the instrument of the achievement which consists of oral reading and comprehension test. The validity of the instrument has been verified. The two researchers have used T-test for two independent samples to analyze data and to identify the significant differences. Results show that the experimental group has outdone the control group in reading achievement in all fields.(Reading validity، speed and comprehension). In the light of the above results، the two researchers have adopted the method of semiotic scansion in teaching Kurdish reading.